Réponses

2013-09-21T12:53:26+02:00
A(x) =(2x + 1)(x - 3) - 4x + 1 = 2x * x + 2x * (-3) + 1 * x + 1 * (-3) - 4x + 1 =  2x^{2} + (-6x) + 1x + (-3) - 4x + 1 =  2x^{2} -9 + 1

C(x) = 2(x - 1)(x + 3) = 2 * x + 2 * (-1) + 2 * x + 2 * 3 = 2x + (-2) + 2x + 6 = 4x + 4

Pour le B, je sais pas faire a cause du carré a la fin.
2013-09-21T12:58:46+02:00
Développement
A= (2x+1)(x-3) -4x +1
     2x² -3x +x -3 -4x +1
     2x² -6x +1

(4x -5)²           identité remarquable (a-b)² = a² -2ab +b²
 16x² -40x +25

2(x-1)(x+3)
2(x² +3x -x -3)
2(x² +2x -3)
2x² +4x -6